PENGARUH MODEL PEMBELAJARAN THINK TALK WRITE BERBANTUAN MIND MAPPING TERHADAP KOMPETENSI PENGETAHUAN IPA KELAS IV - Ni Made Dian Pramita Dewi (Universitas Pendidikan Ganesha, 2018)
The porpuse of this research aimed to know about the effect of think talk write learning model assisted by mind mapping against the natural science competence of grade class elementary scholl of Kompyang Sujana District of North Denpasar in the 2017/2018academic year. This type of research was a quasi-experiment using a nonequivalent control group design. The population of this research were all of the students in the grade of the elementary school in Kompyang Sujana District of North Denpasar containing 350 people. The sample determined by random sampling technique by randomizing the class. The obtained sample was previously equalized using T-test polled variance. Therefore, the sample of this research was the fourth-grade students of SDN 4 Tonja with the total amount of 42 students as the experimental group and the fourth-grade students of SDN 2 Peguyangan containing 47 students as the control group. The knowledge competence data of natural science subject collected by using the instrument in the form of objective test or multiple choice. The test that consisted of 32 items has been validated. The result ofcalculation of “gain” data score showed the average value of science knowledge competence of experimental class students was higher than the average knowledge competence of science students of control class (experimental = 0,52 > control = 0,32). Hypothesis testing was analyzed using the t-test with the formula “polled variance”, and data are prove by the result of tcal = 5.992 > ttab (α = 0.05, 87) = 2,000. The result of the research shows that the learning model of think talk write assisted by mind mapping affects the students’ competence of natural science subject of the fourth-grade in Gugus Kompyang Sujana North Denpasar in the 2017/2018 academic year.